Transition Cow Nutrition and Management Strategies of Dairy Herds in the Northeastern United States: Associations of Nutritional Strategies with Analytes, Health, Milk Yield, and Reproduction - Allison L. Kerwin; Winfield S. Burhans; Daryl V. Nydam; Thomas R. Overton (Animals, 2023)
The objective was to identify relationships between transition cow nutritional strategies and the prevalence of elevated analytes (nonesterified fatty acids (NEFA), β-hydroxybutyrate (BHB), and haptoglobin (Hp)), disorder incidence (DI), milk yield, and reproductive performance. Multiparous and primiparous cows from 72 farms in the northeastern US were enrolled in a herd-level cohort study. Farms were dichotomized within parity into a nutritional strategy within each period; far-off: controlled energy (CE; <16.5% starch and ≥40% forage neutral detergent fiber (FNDF)) or not CE (NCE; ≥16.5% starch or <40% FNDF or both), close-up: high FNDF (HF; ≥40% FNDF) or low FNDF (LF; <40% FNDF), and fresh: low starch (LS; <25.5% starch) or high starch (HS; ≥25.5% starch). No evidence existed that transition cow nutritional strategies were associated with milk yield outcomes (p ≥ 0.20). In general, our results support feeding multiparous cows HF close-up and HS fresh to minimize excessive BHB and DI; however, multiparous cows fed LF close-up had a higher pregnancy rate, and lower prepartum NEFA and Hp. Similarly, our results support feeding primiparous cows CE far-off, HF close-up, and HS fresh to maximize reproductive performance, and minimize BHB and DI; however, herds fed HF close-up or HS fresh had higher Hp.